Accurate quantification of the stability of the perylene-tetracarboxylic dianhydride on Au(111) molecule-surface interface - Ruiz, Victor G.; Wagner, Christian; Maaß, Friedrich; Arefi, Hadi H.; Stremlau, Stephan; Tegeder, Petra; Tautz, F. Stefan; Tkatchenko, Alexandre (Communications chemistry, 2023)
Studying inorganic/organic hybrid systems is a stepping stone towards the design of increasingly complex interfaces. A predictive understanding requires robust experimental and theoretical tools to foster trust in the obtained results. The adsorption energy is particularly challenging in this respect, since experimental methods are scarce and the results have large uncertainties even for the most widely studied systems. Here we combine temperature-programmed desorption (TPD), single-molecule atomic force microscopy (AFM), and nonlocal density-functional theory (DFT) calculations, to accurately characterize the stability of a widely studied interface consisting of perylene-tetracarboxylic dianhydride (PTCDA) molecules on Au(111). This network of methods lets us firmly establish the adsorption energy of PTCDA/Au(111) via TPD (1.74 ± 0.10 eV) and single-molecule AFM (2.00 ± 0.25 eV) experiments which agree within error bars, exemplifying how implicit replicability in a research design can benefit the investigation of complex materials properties.